Characterization of protease-producing bacteria isolated from terasi - Novi Arfarita; Ekachai Chukeatirote (The East Java Biological Society, 2015)
Total of 117 bacterial strains were isolated from terasi samples and 69% of isolates (71) could perform distinctive proteolytic activity that related to the ability to produce protease enzymes. Their proteolytic activity was further tested using spot incubation technique. Strain S4-5 has shown the highest activity then was selected for further tests in this study. Gram staining test showed that S4-5 is gram positive bacteria and able to grow under an aerobic condition. Based on API biochemical profiles, S4-5 strain bacteria was Bacillus licheniformis. Similarity test of genome sequence among Bacillusspecies from gene bank (EMBL Sequence Version) with Bacillusspp., strain S4-5 had similarity with Bacillus licheniformis genome. The optimal pH of this strain was 6 whereas the optimum temperature for Bacillus licheniformis strain S4-5 was 37°C.